KONSEP PENGELOLAAN HOTEL ZAM-ZAM SYARIAH DITINJAU DARI FATWA MUI NOMOR 108/DSN-MUI/X/2016 (STUDI KASUS HOTEL ZAM-ZAM SYARIAH PURBA BARU KEC. LEMBAH SORIK MARAPI) - Muhlisah Lubis; Yusuf Asroi (EKSYA : Jurnal Ekonomi Syariah, 2022)
Commercially, and fulfills the requirements set by the government. One of the components of the sharia tourism industry in the Mandailing Natal district is the Zam-Zam Syariah Hotel. Hotels that are in accordance with sharia principles are hotels which, in providing lodging, eating and drinking services and other services for the public, are managed and do not conflict with sharia principles. In fact, not all of these efforts have implemented sharia principles as a whole in accordance with the Fatwa of the DSN MUI No. 108/DSN-MUI/X/2016 concerning Guidelines for the Implementation of Tourism Based on Sharia Principles. The type of research used is field research (Field Research) with a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. Inductive analysis technique is to draw things that are specific to things that are general. The results of the study state that, First, the prohibition of checking in for non-Muslims by implementing a screening process for hotel guests, Hotel Zam-Zam Syariah provides adequate facilities, equipment, and facilities in the implementation of worship, Hotel Zam-Zam Syariah does not provide entertainment facilities that leads to disobedience such as cafes, karoeke, swimming pools, and therapeutic facilities and only provides entertainment facilities for children. Hotel Zam-Zam Syariah has implemented and used the Ijarah contract with hotel guests. Second, the Sharia Zam Zam Hotel has not complied with the guidelines for establishing sharia tourism as stated in the Fatwa of the DSN MUI No. 108/DSN-MUI/X/2016 concerning Guidelines for the Implementation of Tourism Based on Sharia Principles because it has not met the criteria set by the Indonesian Ulema Council.